Dysregulation of TBX1 dosage in the anterior heart field results in congenital heart disease resembling the 22q11.2 duplication syndrome - Hasten, Erica; McDonald-McGinn, Donna M; Crowley, Terrence B; Zackai, Elaine; Emanuel, Beverly S; Morrow, Bernice E; Racedo, Silvia E (Human molecular genetics, 2018)
Abstract Non-allelic homologous recombination events on chromosome 22q11.2 during meiosis can result in either the deletion (22q11.2DS) or duplication (22q11.2DupS) syndrome. Although the spectrum and frequency of congenital heart disease (CHD) are known for 22q11.2DS, there is less known for 22q11.2DupS. We now evaluated cardiac phenotypes in 235 subjects with 22q11.2DupS including 102 subjects we collected and 133 subjects that were previously reported as a confirmation and found 25% have CHD, mostly affecting the cardiac outflow tract (OFT). Previous studies have shown that global loss or gain of function (LOF; GOF) of mouse Tbx1, encoding a T-box transcription factor mapping to the region of synteny to 22q11.2, results in similar OFT defects. To further evaluate Tbx1 function in the progenitor cells forming the cardiac OFT, termed the anterior heart field, Tbx1 was overexpressed using the Mef2c-AHF-Cre driver (Tbx1 GOF). Here we found that all resulting conditional GOF embryos had a persistent truncus arteriosus (PTA), similar to what was previously reported for conditional Tbx1 LOF mutant embryos. To understand the basis for the PTA in the conditional GOF embryos, we found that proliferation in the Mef2c-AHF-Cre lineage cells before migrating to the heart, was reduced and critical genes were oppositely changed in this tissue in Tbx1 GOF embryos versus conditional LOF embryos. These results suggest that a major function of TBX1 in the AHF is to maintain the normal balance of expression of key cardiac developmental genes required to form the aorta and pulmonary trunk, which is disrupted in 22q11.2DS and 22q11.2DupS.